Preparation and Properties of Anti-Nail-Biting Lacquers Containing Shellac and Bitter Herbal Extract - Chutima Limmatvapirat; Sontaya Limmatvapirat; Siraprapa Chansatidkosol; Wantanwa Krongrawa; Napasorn Liampipat; Sarocha Leechaiwat; Patipat Lamaisri; Lawan Siangjong; Paranee Meetam; Kuntontip Tiankittumrong (International Journal of Polymer Science)
The purpose of the present investigation was to formulate and evaluate anti-nail-biting lacquers consisting of bitter herbal extracts. The hydroalcoholic extracts obtained from Andrographis paniculata and Tinospora crispa were determined for phytochemical constituents, total phenolic contents, antioxidant activities, anti-inflammatory activities, and cytotoxicities. Anti-nail-biting lacquers were prepared by using herbal extracts (bittering agent), shellac (film forming polymer), ethanol (volatile solvent), and other indispensable additives with continuous stirring. Thus, attempts to enhance the film property and bitterness are accomplished by using polyvinylpyrrolidone (PVP K30) as a copolymer and varying concentrations of herbal extracts. Good accepted formulations were established for drying time, pH, viscosity, smoothness of film, film strength, water resistant, and solubility in simulated saliva and evaluated their bitterness in human volunteers. The results revealed that phytochemical constituents including tannins, glycosides, reducing sugars, alkaloids, terpenoids, and flavonoids were found present in both extracts while saponins were only detected in A. paniculata extract. Although T. crispa extract exhibited a significantly higher (p<0.05) total phenolic content and antioxidant activity than A. paniculata extract, it showed lower protein denaturation inhibition property than A. paniculata extract. Because of the potentials of both extracts without cytotoxicity, anti-nail-biting lacquers containing either A. paniculata extract or T. crispa extract were developed and evaluated. Drying time of formulations was 6-11 min with visually seen glossiness of formulation. Formulations of the nail lacquer showed good pH, viscosity, smoothness of film, film strength, water resistant, and solubility in simulated saliva. The formulations displaying no significant cytotoxicity effect on CRL-2076 cells were assessed on healthy human volunteers to compare bitterness and film characteristics. The results revealed that the optimized formulation containing A. paniculata extract could successfully achieve good film forming property and bitterness release which is considered promising for stopping nail biting.